Analisis sektor unggulan Kota Jambi dalam menghadapi Pandemi Covid-19 - Gabriel Simamora, Rio (Jurnal Paradigma Ekonomika, 2022)
In the years 2016-2019, Jambi City economic growth rate was higher than the Jambi Province and National data, but in 2020, it dropped by 8.07 percent and was lower than the Provincial and National figures. The goal of this study is to identify and describe the major revenue-generating industries and competitiveness sectors in the local economy. Then, on pandemic situation, an examination of the leading and competitive sectors with the potential for development is carried out. In the 2016-2020 timeframe the transportation and warehousing industry is the leading sector with the highest average, according to the results of the LQ analysis. According to the SS research, the largest percentage change is in the power and gas procurement sector. The results of the identification can be utilized to assist additional study in order to help the Jambi City economy accelerate and recover in the face of the COVID-19 pandemic.